Effects of fluctuant magnesium concentration on phenotype of the primary chondrocytes. Issue 12 (26th February 2014) - Dou, Yana; Li, Nan; Zheng, Yufeng; Ge, Zigang
Abstract Magnesium (Mg) and its alloys have attracted much research interest as degradable implant materials. Mg ions may enhance phenotype of chondrocytes at optimal concentrations. In this study, we investigated the effects of fluctuant concentrations of Mg ion released from in vitro degradation of pure Mg microspheres on the phenotype of chondrocytes. The chondrocytes were cultured with 250 μg/mL, 500 μg/mL, and 1000 μg/mL of Mg microspheres (75–150 μm) either on tissue culture plates or within alginate hydrogels, with 5, 10, and 20 mM of MgCl2 solution set as the control group. Concentrations of Mg ions and pH values of the culture medium were measured at 3 days' interval. Cytotoxicity was evaluated while glycosaminoglycan (GAG) content and gene expression of collagen type I/II/X, aggrecan were quantified. Results showed that peak concentrations of Mg ion reached 10, 20, 30 mM, respectively, at day 3 in groups containing Mg‐250 μg/mL, Mg‐500 μg/mL, and Mg‐1000 μg/mL, respectively, whereas pH values increased mildly to approximately 8 in all experimental groups. No significant cytotoxic effects were found at day 1 and day 3 in all experimental groups. GAG content increased 6% at day 14 in Mg‐250 μg/mL group in tissue culture plate, but not in the hydrogel culture. Gene expression of collagen type I/II/X and aggrecan in Mg‐1000 μg/mL group decreased significantly when chondrocytes were cultured in cell culture plates. Increase of gene expression of collagen type X in Mg‐250 μg/mL group at day 7 was observed. However, gene expressions of collagen type I/II/X and aggrecan in Mg groups increased significantly at day 7 when chondrocytes were cultured in hydrogels. It was concluded that the phenotype of chondrocytes was regulated with dynamic concentration of Mg ions and pH values in a dose‐ and time‐dependant manners. Fine‐tuned degradation of Mg microspheres could be used to facilitate layered structures of articular cartilage. Furthermore, it would be cautious to extrapolate from results from 2D chondrocyte cultures. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4455–4463, 2014.